2018
DOI: 10.3390/catal8070258
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Co-Pt Bronze for Electrocatalysis in Acidic Media

Abstract: An electron-conducting mixed oxide, Co-Pt bronze was synthesized and examined as a candidate for a highly durable electrocatalyst for both the polymer electrolyte fuel cells and electrolyzers. The motivation of this study comes from the fact that this material has not been studied as an electrocatalyst in acidic media, although past studies showed a high electronic conductivity and a high corrosion resistance. Co-Pt bronze without metallic Pt was obtained by solid-state synthesis and hot aqua regia rinsing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A common approach to reducing the cost of polymer electrolyte systems is to reduce the Pt loading in the system, which can be done through either a change in catalyst or a change in architecture. On the catalyst side, Co-Pt bronzes were shown to have very good activity and stability whilst significantly reducing the amount of Pt in the catalyst layer [1]. Related to the electrode architecture, two papers explored fundamentally different methods for manipulating the pore structure of the support.…”
mentioning
confidence: 99%
“…A common approach to reducing the cost of polymer electrolyte systems is to reduce the Pt loading in the system, which can be done through either a change in catalyst or a change in architecture. On the catalyst side, Co-Pt bronzes were shown to have very good activity and stability whilst significantly reducing the amount of Pt in the catalyst layer [1]. Related to the electrode architecture, two papers explored fundamentally different methods for manipulating the pore structure of the support.…”
mentioning
confidence: 99%
“…The concentrations of the doped elements in the CMMTOs and the Pt loadings of the Pt/CMSbTOs were determined by using ICP-OES (PS3520UVDD II, Hitachi High-Tech). The electrical conductivities of the CMMTOs were measured using a compression cell 61 and potentiostat (SP-300, Biologic) at a compression pressure of 2.4 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…[41] Indeed, the Co-Pt bronze with Pt in oxidized state exhibited enhanced acidic OER activity compared to the metallic Pt. [274] Guo et al reported Rh-Ir alloy nanoparticles as efficient acidic OER catalyst. By optimizing the Ir content, a maximum mass activity with threefold enhancement relative to pure Ir nanoparticles was achieved.…”
Section: Other Pt-group-metal-based Catalystsmentioning
confidence: 99%
“…[ 41 ] Indeed, the Co–Pt bronze with Pt in oxidized state exhibited enhanced acidic OER activity compared to the metallic Pt. [ 274 ] Guo et al. reported Rh–Ir alloy nanoparticles as efficient acidic OER catalyst.…”
Section: Noble‐metal‐based Acidic Oer Catalystsmentioning
confidence: 99%